Synodontia between maxillary central incisor and a supernumerary incisor teeth: a dental, genetic and dermatoglyphic study - (:unkn) unknown (My University, 1996)
This case report contains the dental, genetic and dermatoglyphic findings of a patient showing bilateral maxillary central incisors fused to an extra one and his paternal uncle having macrodontia of central incisor teeth.
Keywords: Adult; Humans; Infant; Male; Maxilla; Tooth, Deciduous; Incisor; Pedigree; Dermatoglyphics; Tooth, Supernumerary; Fused Teeth